How letter order is encoded in bilingual reading? The role of deviant-letter position in cognate word recognition - Comesaña, Montserrat (2018)
Objective: Previous literature in the monolingual domain has showed that letter position is not encoded in an absolute-position manner. However, with the exception of the unpublished work by Font [(2001). Rôle de la langue dansl’accès au lexique chez les bilingues: Influence de la proximité orthographique et sémantique interlangue surla reconnaissance visuelle de mots (Unpublished Doctoral thesis). Université Paul Valery, Montpellier)], there is no study investigating this issue with bilinguals. According to Font, the recognition of cognate words is affected by the position of the deviant letter. This calls the validity of the input-coding scheme of the most relevant computational model of bilingual word recognition (The Bilingual Interactive Activation Plus Model [BIA+; Dijkstra, T., & vanHeuven, W. J. (2002). The architecture of the bilingual word recognition system: From identification to decision. Bilingualism: Language and Cognition, 5, 175–197. doi:10.1017/S1366728902003012; Dijkstra, T., Miwa, K., Brummelhuis, B., Sappelli, M., & Baayen, H. (2010). How cross-language similarity and task demands affect cognate recognition. Journal of Memory and Language, 62, 284–301. doi:10.1016/j.jml.2009.12.003]) into question, since it holds that letter positions are perfectly encoded. The aim of the present research was to further examine the way letter position is encoded during non-native reading by manipulating the deviant-letter position of European Portuguese (EP)-English (EN) cognate words. Method: To that purpose 288 stimuli (144 Portuguese-English translation words [72 cognates and 72 noncognates] and 144 pseudowords) were selected. Cognates were assigned to two experimental conditions according to deviant-letter position: 1) at end of the word (matriz- MATRIX); and 2) at the beginning of the word (coala-KOALA). A third condition varying both at the beginning and at the end (e.g., escala-SCALE) was also included as a control to test how the degree of cross-language overlap modulates the results. Twenty-eight proficient Portuguese-English bilinguals were asked to perform a masked priming lexical decision task in English. Results: The results revealed faster responses for cognates with greater degree of crosslanguage overlap (Conditions 1 and 2). More important, priming effects were not modulated by deviant-letter position, i.e., the size of priming was similar across condition 1 and 2. Conclusion: Although a priori, no amendments seems to be needed in the “front-end” of the coding scheme of the BIA+ model when cognate words are considered, future studies should be developed in order to explore if these results are restricted to outer deviant-letters.